Ekomarturia - Saefatu, Meyrlin (Sekolah Tinggi Teologi Jaffray Jakarta, 2024)
The life of the world today is faced with cases of ecological damage. For this reason, efforts are needed to prevent it which initially begins with changing the paradigm or perspective so that it leads to how our attitude approaches nature. Are we going to stick to anthropocentrism or do we choose to be ecocentrism and theocentrism but in circumstances that pretend to be concerned about nature when in fact we ourselves are undermining the order of God's creation? Or do we see creation as our brothers that God created to praise His glory? For this reason, this paper will examine the concept of Ecomarturia which is expected to complement and even update the concept of an approach to nature. Researchers use qualitative study methods with the proximity of literature reviews. The results show that nature is our brother as a whole creation that is also created to testify and tell the deeds of God's hand. The approach is called Ecomarturia using a theory based on the Encyclical Laudato Si', Calvin's understanding, and Perikhoresis's theory.